2016
DOI: 10.1017/s0022149x16000778
|View full text |Cite
|
Sign up to set email alerts
|

Increased IgG antibody responses to excretory/secretory antigens in neonates born from mothers infected with filarial nematodes

Abstract: The present investigation aimed to evaluate the extent to which maternal filarial infection influences IgG subclass immune responses in the cord blood of neonates. Prevalence of antigenaemia was detected using an Og4C3 assay. Filaria-specific IgG subclasses against excretory/secretory antigens were measured by ELISA. Transplacental transfer of circulating filarial antigen (CFA) was observed from 34.8% of CFA-positive mothers to their respective cord bloods. Filaria-specific IgG1, IgG2 and IgG4 responses were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Fetally memory T cells have been also found in uninfected children born to mothers infected with human immunodeficiency virus (HIV) ( 91 ), hepatitis B virus (HBV) ( 92 ), hepatitis C virus (HCV) ( 93 ), or plasmodium ( 94 ). In endemic regions, it has been observed that maternal infection by helminths, including filariasis ( 95 ), schistosomiasis ( 96 ), onchocerciasis ( 97 ), and ascariasis ( 98 ) was associated with fetal lymphocytic responses and the consequent production of specific immunoglobulins. If fetal immune cells respond to antigens of infectious agents carried by the mother, it seems reasonable that the fetal immune system may also respond to maternal antigen exposure to pathogens.…”
Section: How Maternal Vaccination Impacts the Immune System In Early Lifementioning
confidence: 99%
“…Fetally memory T cells have been also found in uninfected children born to mothers infected with human immunodeficiency virus (HIV) ( 91 ), hepatitis B virus (HBV) ( 92 ), hepatitis C virus (HCV) ( 93 ), or plasmodium ( 94 ). In endemic regions, it has been observed that maternal infection by helminths, including filariasis ( 95 ), schistosomiasis ( 96 ), onchocerciasis ( 97 ), and ascariasis ( 98 ) was associated with fetal lymphocytic responses and the consequent production of specific immunoglobulins. If fetal immune cells respond to antigens of infectious agents carried by the mother, it seems reasonable that the fetal immune system may also respond to maternal antigen exposure to pathogens.…”
Section: How Maternal Vaccination Impacts the Immune System In Early Lifementioning
confidence: 99%
“…In endemic regions, in utero sensitization to helminths has also been demonstrated by the detection of fetal lymphocyte responses to parasite antigens and the detection of specific immunoglobulins in cord blood. These include filariasis ( 20 ), schistosomiasis ( 21 ), onchocerciasis ( 22 ), and ascariasis ( 23 ). In utero exposure to helminths may also influence the neonatal response to subsequent vaccinations.…”
Section: Transfer Of Infectious Antigens and Allergens During Pregnanmentioning
confidence: 99%